CURRENT USES AND FUTURE CHALLENGES FOR ZEOLITE IN THE INDONESIAN OIL AND GAS PROCESSING INDUSTRY - A.S. Nasution; Chairil Anwar; E. Jasjfi (Scientific Contributions Oil and Gas, 1999)
Oil and gas industry uses zeolite as an adsorbent to reduce moisture content of natural gas in LNG Plant, and as catalyst to convert the heavy petroleum fractions feeds into light clean fuels in refinery.Low quality crude oil, low residual fuel demand, and an increased demands and spesifications for light products (gasoline, kerosene, and diesel oil) and petrochemical products, future challenges for utilization zeolite as cracking catalyst in refinery are encouraging.